Clinical and molecular characteristics of infantile-onset diabetes mellitus in Egypt - Yasmine Abdelmeguid; Ehsan Wafa Mowafy; Iman Marzouk; Elisa De Franco; Shaymaa ElSayed (Korean Society of Pediatric Endocrinology, 2022)
Purpose In patients diagnosed with diabetes mellitus (DM) before the age of 12 months, there is an increasing recognition of diabetes caused by single-gene mutations, also known as monogenic diabetes of infancy or neonatal DM (NDM). This study aimed to classify patients at Alexandria University Children's Hospital (AUCH) diagnosed with infantile-onset DM into type 1 DM (T1DM) or NDM and to detect differences in molecular characteristics of NDM patients at our center in comparison to other countries. Methods This retrospective/prospective observational study was conducted on 39 patients diagnosed with infantile-onset DM (age of onset ≤1 year) at AUCH from January 2003 to November 2020. The patients were divided into 2 groups according to age at the onset of DM: ≤6 months and >6-12 months. Molecular testing was done in patients diagnosed with DM at ≤6 months and those with negative autoantibodies. Results Twelve patients were diagnosed with DM at age ≤6 months and 27 patients were diagnosed between 6-12 months. Seventeen patients (43.6%) had T1DM, whereas 9 patients (23.1%) had genetically confirmed NDM, including 3 harboring novel mutations. The most common genetic causes of NDM were EIF2AK3 mutations (n=3), followed by KCNJ11 (n=2) and ABCC8 (n=2). Other mutations included SLC19A2 (n=1) and INS (n=1). Three patients with potassium ATP channel mutations were transferred from insulin to sulfonylurea treatment. Conclusions It is essential to identify patients with NDM clinically and confirm the diagnosis by molecular testing to distinguish them from T1DM as it helps in refining their management, predicting prognosis, and guiding genetic counseling.